Using Cochlear Microphonic Potentials to Localize Peripheral Hearing Loss - Charaziak, Karolina K.; Shera, Christopher A.; Siegel, Jonathan H. (Frontiers in Neuroscience, 2017)
The cochlear microphonic (CM) is created primarily by the receptor currents of outer hair cells (OHCs) and may therefore be useful for identifying cochlear regions with impaired OHCs. However, the CM measured across the frequency range with round-window or ear-canal electrodes lacks place-specificity as it is dominated by cellular sources located most proximal to the recording site (e.g., at the cochlear base). To overcome this limitation, we extract the “residual” CM (rCM), defined as the complex difference between the CM measured with and without an additional tone (saturating tone, ST). If the ST saturates receptor currents near the peak of its excitation pattern, then the rCM should reflect the activity of OHCs in that region. To test this idea, we measured round-window CMs in chinchillas in response to low-level probe tones presented alone or with an ST ranging from 1 to 2.6 times the probe frequency. CMs were measured both before and after inducing a local impairment in cochlear function (a 4-kHz notch-type acoustic trauma). Following the acoustic trauma, little change was observed in the probe-alone CM. In contrast, rCMs were reduced in a frequency-specific manner. When shifts in rCM levels were plotted versus the ST frequency, they matched well the frequency range of shifts in neural thresholds. These results suggest that rCMs originate near the cochlear place tuned to the ST frequency and thus can be used to assess OHC function in that region. Our interpretation of the data is supported by predictions of a simple phenomenological model of CM generation and two-tone interactions. The model indicates that the sensitivity of rCM to acoustic trauma is governed by changes in cochlear response at the ST tonotopic place rather than at the probe place. The model also suggests that a combination of CM and rCM measurements could be used to assess both the site and etiology of sensory hearing loss in clinical applications.